CONSTITUTIONAL HERMENEUTIC: A FAITH IN CONSTITUTION INTERPRETATION - M. Ilham Hermawan (Diponegoro Law Review, 2016)
Hermeneutics can be used as a foundation of understanding on the interpretation of the constitution. Hermeneutic goal is not to develop a set of rules or procedures (methods) on textual interpretation, but as meta in the interpretation. Problems of constitutional interpretation cannot be blasted between theories that exist in the interpretation of the constitution. Clash between theories will not be able to resolve the constitutional issue. Each theory has a foundation of rationality and justification of each method. Therefore, the settlement should be drawn more into the realm of deep again, i.e. into the realm of ontology. The purpose is not to develop a set of rules or procedures on the interpretation of the text “method (be cognitive)” but the search for answers to no interpretation itself “ontis”. So objectivity lies in philosophy, then identified “not on what we do or we should do (in interpretation), but what happens to us other than what we want and do”. So it is clear that the hermeneutic assemble themselves on things that are ontological, and identify relationships that cannot be changed between the reader with the text, in the past and the present, which appears at the beginning of understanding. Keywords : constitutional, hermeneutic, constitution interpretation